The importance of localized hunting of diverse animals to early inhabitants of the Eastern Tibetan Plateau at the Neolithic site of Xiaoenda. (20th September 2019) - Zhang, Zhengwei; Chen, Zujun; Marshall, Fiona; Lü, Hongliang; Lemoine, Ximena; Wangyal, Tashi; Dorje, Tsepa; Liu, Xinyi
Abstract: Understanding of when and how human groups engaged with and settled different regions of the Tibetan Plateau has been greatly extended in the past decade. Research on the mid/late Holocene has focused on the roles of material cultural traditions and cropping systems in the process of long-term settlement. In this paper, we shift the focus to explore animal -based subsistence strategies used to adapt to life on the eastern Tibetan Plateau. Dated to between 5000 and 4000 cal. BP, Xiaoenda represents one of the oldest Neolithic sites known in this region. New zooarchaeological data from Xiaoenda reveals that the site's inhabitants relied on a diverse array of wild animal taxa. This contrasts with previous assertions regarding the role of domestic animals in this region. Xiaoenda's location between highland and multiple lower elevation catchment zones allowed access to a range of wild prey species. Zooarchaeological data indicate that the inhabitants of Xiaoenda took advantage of this, practicing a diverse localized hunting strategy. Our findings demonstrate that people at Xiaoenda depended on wild rather than domestic animals and indicate a role for wild game in facilitating continuous occupation in the eastern Tibetan Plateau during the fifth millennium BP.